Religious education in the abroad educational system - Мустaфaевa, A. A. (Journal of Oriental Studies, 2017)
This article attempts to examine the phenomenon of religious education in several European and Asian countries. Each state depending on the selected policy defines the status of religion in general and religious education in particular. Religious education depending on the status of the state in every country passes its history periods and carried out differently. So, the first countries where the functioning state and church, religious education is compulsory; in the second countries, where they are separated (a state from a religion or a church from a state) religious education is forbidden, and in the last - third, where between state and religion established relationships, religious education carried out on through a series of agreements like harmony.